Stroke Unit : Does it make a difference ? Assessment of the early effectiveness of a Stroke Unit in improving functional state in Dr. Cipto Mangunkusumo Hospital (Medical Journal of Indonesia, 2006)
Abstact Stroke unit has been believed as the best institutional care for stroke patients. Recent researches in 1990s indicated that stroke units can produce increasing survival rate and improving the functional state of the patients which can reduce the need for institutional care after stroke. In Indonesia, stroke unit is still new. Because stroke unit has educational role beside its clinical importance, the research about stroke unit especially in its value in managing stroke patients in Indonesia is needed. This study was evaluated the effectiveness of stroke unit care in managing stroke patients especially in improving the functional state of the patients in compared with conventional care of stroke corner in general neurology ward. This study indicated that both stroke unit (SU) and stroke corner in general neurology ward (SC) shows reduction in NIHSS score. In Stoke Unit, the reduction of NIHSS was 17.35 to 5.31 while in Neurology ward from 13.83 to 8.87.Using independent t-test, the reduction of NIHSS in stroke unit is more significance compared with stroke corner in general neurology ward (p=0,000). (Med J Indones 2006; 15:30-3)Keywords: Stroke Unit, General Neurology Ward, NIHSS